Geografia e justiça ambiental: estudo de capacidade de suporte do Quilombo da Fazenda - Danilo Santos da Silva; João Osvaldo Rodrigues Nunes (Confins)
This paper uses the Physical Geography approach to analyze the environmental complexities of an area located in the coastal plain of the Serra do Mar. The quilombola territory (territory of quilombos inhabitants), from its historical, social and cultural formation, to contextualize the process of evolution of natural systems, the territorial conflict and the production of geographical space, focusing on the legal decision process for the State to recognize quilombola territory. The Quilombo da Fazenda, in Ubatuba, is located in an area overlapping the State Park of Serra do Mar. Technical, scientific and legal limitations hinder the definitive, official recognition of the quilombola territory. The research will contribute to resolve the technical impasse and generate social changes capable of promoting environmental justice in the region. Based on the methodological approach, it concluded that on the spots where historically the Quilombo da Fazenda community use the land, there are an positive influence emerge on the composition of forest fragments, i.e., increase in number of species and stability of erosive morphodynamic processes and gravitational mass. The combined dynamic among soil, earth surface and forest, results in physical and biotic conditions that can subsidize the analysis of environmental support capacity of the area, an essential required prerequisite for the State to recognize the quilombola territory. Using Ecodynamics criteria, namely geostatistical modeling combining susceptibility data of gravitational movements of mass, slope, and flood, with the occurrence of species and forest richness, the study classified three different environmental support capacity high, medium and low.